Highly Conductive and Strain‐Released Hybrid Multilayer Ge/Ti Nanomembranes with Enhanced Lithium‐Ion‐Storage Capability. (26th October 2012) - Yan, Chenglin; Xi, Wang; Si, Wenping; Deng, Junwen; Schmidt, Oliver G.
<x xml:space="preserve">Abstract</x> Highly conductive and hybridized microtubes relying on strain‐released ultrathin Ti/Ge bilayer nanomembranes are reported. These hybrid multilayer microtubes show a remarkably enhanced reversible capacity up to 1495 mA h g−1 with a high first‐cycle Coulombic efficiency of 85%, and demonstrate an excellent capacity of ≈930 mA h g−1 after 100 cycles. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>